Crimea – the Beginning of the End - Andreea-Ioana Cozianu (CES Working Papers, 2014)
The present approach studies the probability of the decomposition of the current international geopolitical system in the context of the EU's socio-economical and political stagnation. We do not intend to say that European Union represents the determinant factor for the system's decomposition, since we have not found EU as a major player on the International Relations arena, but we are more pointing out that EU's dream to recover a lost greatness will not so soon fulfil. We also intend to refer to those elements that actually connect EU to a changing world: competitive human resources engaged in the market economy, and hardly its values, like the promotion of the human rights and democracy. So, is it possible to play by the rules and be regarded as a powerful player on the same time?! International Relations system diversity makes it almost impossible. (Neo)Liberal concepts like “democratic peace” or “international institutions”, the promotion of the human rights and of democracy get pale in the face of a reality dominated by an emerging Russian Federation that plays by the (Neo) Realism power commandments. And so we get to deal with the Ukrainian situation where to each Western sanction, The Russian Federation opposes a “tank”.
Keywords: F5; 330; Crimea; European Neighbourhood Policy; (Neo)Realism versus (Neo)Liberalism; Russia as an emerging power; the value of the international interdependence; the new international actors on IR scene Romania